Added Masses of Ship Structures - Korotkin, Alexandr I. (Fluid Mechanics and Its Applications, 2009)
Knowledge of added body masses that interact with fluid is necessary in various research and applied tasks of hydro- and aeromechanics: steady and unsteady motion of rigid bodies, total vibration of bodies in fluid, local vibration of the external plating of different structures. This reference book contains data on added masses of ships and various ship and marine engineering structures. Also theoretical and experimental methods for determining added masses of these objects are described. A major part of the material is presented in the format of final formulas and plots which are ready for practical use. The book summarises all key material that was published in both in Russian and English-language literature. This volume is intended for technical specialists of shipbuilding and related industries. The author is one of the leading Russian experts in the area of ship hydrodynamics.